X+-1/7x=48

Simple and best practice solution for X+-1/7x=48 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for X+-1/7x=48 equation:



X+-1/7X=48
We move all terms to the left:
X+-1/7X-(48)=0
Domain of the equation: 7X!=0
X!=0/7
X!=0
X∈R
determiningTheFunctionDomain X-1/7X-48+=0
We add all the numbers together, and all the variables
X-1/7X=0
We multiply all the terms by the denominator
X*7X-1=0
Wy multiply elements
7X^2-1=0
a = 7; b = 0; c = -1;
Δ = b2-4ac
Δ = 02-4·7·(-1)
Δ = 28
The delta value is higher than zero, so the equation has two solutions
We use following formulas to calculate our solutions:
$X_{1}=\frac{-b-\sqrt{\Delta}}{2a}$
$X_{2}=\frac{-b+\sqrt{\Delta}}{2a}$

The end solution:
$\sqrt{\Delta}=\sqrt{28}=\sqrt{4*7}=\sqrt{4}*\sqrt{7}=2\sqrt{7}$
$X_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(0)-2\sqrt{7}}{2*7}=\frac{0-2\sqrt{7}}{14} =-\frac{2\sqrt{7}}{14} =-\frac{\sqrt{7}}{7} $
$X_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(0)+2\sqrt{7}}{2*7}=\frac{0+2\sqrt{7}}{14} =\frac{2\sqrt{7}}{14} =\frac{\sqrt{7}}{7} $

See similar equations:

| 3y+7=5y-6 | | 2k=k-6/2 | | 34=4w-10 | | 8(x+9=88 | | 3x²-20x+12=0 | | 50=5(x=+50 | | |3x+12|=26 | | (3)(2^x)=(2)(5^x) | | x-(x*0,25)=1500 | | -75x+24=-26 | | 2.7x3.8=10.26 | | X=5y+9/6 | | 3x+4=-7x-24 | | 6x+19=10x-9 | | 6x-+19=10x-9 | | 2x+14=-x+32 | | 10x+4=5x+34 | | 10x+9=3x-40 | | (x÷2-x÷5)=12 | | A+B=(AxB)+A | | 2(3x+4)+3(x+5)=50 | | x÷2-x÷5=12 | | 5x-6=2x-26 | | 7×(2x-1)=35 | | 6x+8+3x+15=50 | | 3×(5x+2)=21 | | 9x9=19 | | x2-7=42 | | (3x+6)÷5=-6 | | 4(3x+2)=5(2x-6) | | 1-6a=2a7 | | -2t+10=2t−2 |

Equations solver categories